Comparative analysis of TPVB and ESPB for postoperative pain management in thoracic and breast surgeries - Moeez Akram; Muhammad Rehan Iftikhar; Quratulain Fatima; Muhammad Ubaida; Hareem Khan; Hadia Mohsin; Muhammad Ibrahim; Muhammad Abdullah Hassan Wattoo; Muhammad Uzair Tahir; Marsad Ali (Future Science OA)
Objective This meta-analysis assesses the efficacy and safety of erector spinae block (ESPB) and paravertebral block (PVB) for managing postoperative pain in thoracic and breast surgeries.Design Data from 12 randomized controlled trials (RCTs) published between 2019 and 2022 were included, and selected based on stringent criteria.Setting The RCTs were conducted across various clinical settings, including operating theaters worldwide.Patients The analysis involved 844 patients undergoing thoracic or breast surgery under regional anesthesia, representing diverse health statuses.Interventions Patients received either PVB or ESPB, typically guided by ultrasound, for postoperative pain control.Main Findings PVB demonstrated superior pain management during rest and mobility, requiring fewer additional analgesics than ESPB. Incidences of postoperative nausea and vomiting (PONV) and opioid consumption did not differ significantly between the methods. ESPB showed more effective block placement.Conclusion PVB is preferred for reducing analgesic requirements and managing postoperative pain, especially during rest and activity. ESPB offers advantages in block placement. Surgical type and patient preferences should guide the choice between PVB and ESPB, necessitating further research for optimized clinical application.